Upaya Edukasi Fisioterapi Tentang Masalah Trigger Finger pada Lansia di Posyandu Desa Watugede RW.04 Kecamatan Singosari - Wildanul Nafis, Nawwaf; Hasta Baruna, Arys; Vidya Amelia, Ratna (Jurnal Kesehatan Masyarakat Indonesia (JKMI), 2025)
Aging represents a decline in the ability of body tissues to repair and maintain their structure and function. A decrease in endurance will lead to a decrease in muscle mass. In addition, older people are more susceptible to diseases as their immune system declines. The elderly often experience diseases such as diabetes mellitus, stroke, hypertension, arthritis, and more. With aging, organ functions and activities performed will decrease, and some elderly people may experience many health problems, including musculoskeletal problems such as trigger finger. The most common finger disorder is the trigger finger. This is caused by inflammation, which causes the flexor tendon sheath to thicken and narrow the space between the retinal sheaths of the cicle. This condition causes pain, a clicking sound when the finger is pulled and retracted, and the affected finger is locked or immobilized. This condition occurs because the protective sheath around the tendon ruptures. It can occur due to pressure on the finger area, such as carrying a briefcase or shopping bag, or grasping tools with sharp or blunt edges. Some people attribute the cause of trigger finger to multifactorial causes because everyone's fingers are always moving. The movement of the swollen tendon sheath causes inflammation of the tendon sheath surrounding the flexor tendon of the finger.